Generation of Multipotential NG2 Progenitors From Mouse Embryonic Stem Cell-Derived Neural Stem Cells - Otsu, Masahiro; Ahmed, Zubair; Fulton, Daniel (Frontiers in Cell and Developmental Biology, 2021)
Embryonic stem cells (ESC) have the potential to generate homogeneous immature cells like stem/progenitor cells which appear to be difficult to isolate and expand from primary tissue samples. In this study we developed a simple method to generate homogeneous immature oligodendrocyte (OL) lineage cells from mouse ESC-derived neural stem cell (NSC). NSC converted to NG2+ /OLIG2+ double positive progenitors (NOP) after culturing in serum-free media for a week. NOP expressed Prox1, but not Gpr17 gene, highlighting their immature phenotype. Interestingly, FACS analysis revealed that NOP expressed proteins for NG2, but not PDGFRα distinguishing them from primary OL progenitor cells (OPC). Nevertheless, NOP expressed various OL lineage marker genes including Cspg4, Pdgfrα, Olig1/2, Sox9/10, but not Plp1 genes, and when cultured in OL differentiation conditions, initiated transcription of Gpr17 and Plp1 genes, and expression of PDGFRα proteins, implying that NOP converted into a matured OPC phenotype. Unexpectedly, NOP remained multipotential, being able to differentiate into neurons as well as astrocytes under appropriate conditions. Moreover, NOP-derived OPC myelinated axons with a lower efficiency when compared with primary OPC. Taken together these data demonstrate that NOP are an intermediate progenitor cell distinguishable from both NSC and primary OPC. Based on this profile, NOP may be useful for modelling mechanisms influencing the earliest stages of oligogenesis, and exploring the cellular and molecular responses of the earliest OL progenitors to conditions that impair myelination in the developing nervous system.